Effectiveness of Law Enforcement Against Criminal Acts of Corruption in Public Services Based on Law Number 25 of 2009 Concerning Public Services - Amiruddin, Sulaiman; Riswadi, Riswadi (International Journal Labs, 2025)
This research examines the effectiveness of law enforcement against corruption in public services under Law Number 25 of 2009 concerning Public Services in Indonesia. Corruption in public services, such as bribery, extortion, and abuse of authority, undermines good governance and public trust. The study aims to analyze the role of the Public Service Law as a legal framework for combating corruption and evaluate the challenges in law enforcement. Using a normative juridical method, the research analyzes legal norms, regulations, and literature, including the Public Service Law and the Criminal Code. Findings reveal that while the Public Service Law provides a robust administrative and ethical foundation for public services, violations often escalate into criminal corruption. Key challenges include weak internal supervision, low public reporting due to fear, and complex bureaucratic procedures. The study highlights the need for stronger coordination between institutions like the Corruption Eradication Commission (KPK), the Ombudsman, and law enforcement agencies. Implications suggest systemic reforms, such as digitalizing public services to reduce corruption opportunities, enhancing whistleblower protections, and improving law enforcement capacity. These measures are crucial for fostering transparency, accountability, and public trust in government services.